Ulam-Hyers Stability Results of λ-Quadratic Functional Equation with Three Variables in Non-Archimedean Banach Space and Non-Archimedean Random Normed Space - Ly Van An; Kandhasamy Tamilvanan; R. Udhayakumar; Masho Jima Kabeto; Ly Van Ngoc (Journal of Function Spaces)
In this paper, we introduce the λ-quadratic functional equation with three variables and obtain its general solution. The main aim of this work is to examine the Ulam-Hyers stability of this functional equation in non-Archimedean Banach space by using direct and fixed point techniques and examine the stability results in non-Archimedean random normed space.